Crystal structure of the ZrO phase at zirconium/zirconium oxide interfaces - Nicholls, R; Ni, N; Lozano-Perez, S; London, A; McComb, D; Nellist, P; Grovenor, C; Pickard, C; Yates, J (Wiley, 2014)
© 2014 Rebecca J. Nicholls, Published by Wiley-VCH Verlag GmbH and Co. KGaA. Zirconium-based alloys are used in water-cooled nuclear reactors for both nuclear fuel cladding and structural components. Under this harsh environment, the main factor limiting the service life of zirconium cladding, and hence fuel burn-up efficiency, is water corrosion. This oxidation process has recently been linked to the presence of a sub-oxide phase with well-defi ned composition but unknown structure at the metal-oxide interface. In this paper, the combination of first-principles materials modeling and high-resolution electron microscopy is used to identify the structure of this sub-oxide phase, bringing us a step closer to developing strategies to mitigate aqueous oxidation in Zr alloys and prolong the operational lifetime of commercial fuel cladding alloys.